Distal Humerus as Delayed Site of Metastasis from Small Cell Carcinoma of Gallbladder - Mutahir A. Tunio; Mushabbab AlAsiri; Asma Mohammed F. Ali; Eyad Fawzi AlSaeed; Muhammad Shuja; Hanadi Fatani (Case Reports in Gastrointestinal Medicine)
Background. Small cell carcinoma (SCC) of the gallbladder is a rare entity and is often seen in elderly women. SCC of gallbladder is typically a nonsecretory carcinoid tumor without overt clinical symptoms and is often discovered at advanced stages. SCC of gallbladder carries a dismal prognosis as compared to SCC of lung and adenocarcinoma of gallbladder. To date, only 73 case reports have been published in the world literature. Case Presentation. Herein, we report a case of a 73-year-old Saudi woman who presented with one week history of right upper quadrant abdominal pain and obstructive jaundice and was found to be a case of locally advanced, metastatic SCC of gallbladder cT4N1M1 (liver, para-aortic lymph nodes, and bone). The patient was treated with neoadjuvant etoposide and cisplatin (EP) chemotherapy three cycles after biliary stenting followed by radical cholecystectomy, lymphadenectomy, and adjuvant EP chemotherapy and then one year later developed distal humerus osseous metastasis. Conclusion. SCC of the gallbladder is very rare entity and is often seen at advanced stages. Osseous metastases of peripheral skeleton from SCC gallbladder are rarely reported. Surgery is curative option but only for early stage tumors. Incorporation of chemotherapy along with radical resection increases the survival.